La mise en culture des « jardins de luxe » parisiens pendant la Terreur (1793-1795) - Clara Delannoy (Les Cahiers de l'École du Louvre)
One of them concerns the typological change and sometimes disappearance of the vast groups of private gardens in the seventh arrondissement of Paris during the French Revolution. The hypothesis to explain these changes explored here concerns the cultivation of these gardens, considered a luxury, as a response to the famine of 1793. The updating of the archives of the Régie des Biens Nationaux, kept in the Archives de Paris, has shed light on the gardens belonging to nationalised properties in the city of Paris. A new resource to be developed, the “luxury gardens” underwent numerous upheavals linked both to the symbolism of the Ancien Régime that they embodied and to the new nuances brought to the notion of public space by the French Revolution.